PTU-044 Is there any value in performing a clo test at endoscopy in patients previously having a stool antigen test?. (22nd June 2015) - Dhesi, E; White, B; Chitembwe, A; Alisa, A; Musa, S; Besherdas, K
Abstract : Introduction: Helicobacter pylori (HP) infection is causally associated with gastritis, peptic ulcer disease, mucosal associated lymphoid tissue and gastric malignancy. Current 'test and treat' guidelines for dyspepsia recommend the non-invasive testing by way of stool antigen test (SAT) for diagnosis of HP, prior to eradication therapy. We observed that in clinical practice most patients attending upper gastrointestinal endoscopy for dyspepsia have HP testing at endoscopy by way of CLO ( Campylobacter -Like-Organism) test. There is increasing evidence, however, that the CLO test has lower diagnostic accuracy (sensitivity 80%, specificity 90%) in comparison to the SAT (sensitivity 96%, specificity 98%). We hypothesised that there was no additional diagnostic value in a CLO test, if a patient had already undergone stool antigen testing prior to endoscopy. Method: A single centre (north London endoscopy unit), retrospective analysis of 98 consecutive patients who had undergone stool antigen testing prior to a CLO test at OGD, for the investigation of dyspeptic symptoms was undertaken. The electronic patient record was scrutinised to compare the result of the CLO test and SAT in these patients. Of those who were stool antigen positive, it was noted whether they were documented to have received eradication therapy prior to their endoscopy. Results: A total of 81 out of 98 patients tested (82.7%), were SAT negative. Within the cohort of stool antigen negative patients, 98.8% were also CLO test negative (80/81). CLO testing in the presence of a negative SAT detected one additional case of H. Pylori infection (1.2%, 1/81). Within the cohort of SAT positive patients (17/98 total patients), 35.3% (6/17) were CLO test positive. Only one of these patients had not been documented to receive eradication therapy prior to their CLO test. Conclusion: In our study, 96 of 98 patients (98.0%) did not directly benefit from CLO testing, following stool antigen testing. CLO testing provided new diagnosis of H.pylori infection in only 1 out of the 98 cases, where SAT had already been undertaken. This study proves our hypothesis to be valid in 99.0% of the cases reviewed. We recommend that a CLO test should not be performed at endoscopy, if the SAT result is already available. This will help reduce the financial cost of obtaining the CLO test (biopsy NHS tariff plus CLO test cost, equating to £40 per patient) and also reduce the administration time associated in documentation of the CLO test result. Disclosure of interest: None Declared.